2020
DOI: 10.1192/j.eurpsy.2020.86
|View full text |Cite
|
Sign up to set email alerts
|

Can loss of agency and oppositional perturbation associated with antidepressant monotherapy and low-fidelity psychological treatment dilute the benefits of guideline-consistent depression treatment at the population level?

Abstract: Despite major expansions of evidence-based treatments of common mental disorders in recent decades, especially antidepressant medication, the point prevalence of depression has not decreased; instead it probably increased in young adults. We question whether antidepressants (AD)-monotherapy and low-fidelity-to-guideline psychological treatment (PT) might have no effect or even adverse effects in some patients and contexts that dilute the benefits of treatment at the population level, making it harder for popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In turn, these problems may have compromised effectiveness of Australia's mental health service delivery system quality (28,29), impacted by inequity in service delivery and forms of iatrogenesis (17,75). A lack of data precludes the analysis of service quality across much of the service system and this itself is a problem (62).…”
Section: Inequity Ineffectiveness and Iatrogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…In turn, these problems may have compromised effectiveness of Australia's mental health service delivery system quality (28,29), impacted by inequity in service delivery and forms of iatrogenesis (17,75). A lack of data precludes the analysis of service quality across much of the service system and this itself is a problem (62).…”
Section: Inequity Ineffectiveness and Iatrogenesismentioning
confidence: 99%
“…Perhaps inequitable and lower quality treatment for mental health problems may actually do some harm as well as good. It has been suggested that iatrogenic influences based on a loss of agency arising from medicalization might perhaps negate the relatively modest effect of antidepressant monotherapy (17,75,76). It also has been proposed that antidepressants themselves may have a significant property of oppositional perturbation, so increasing the rates of depression among those who have been prescribed them above the rates that would have been observed had they never been exposed to this therapy (75).…”
Section: Inequity Ineffectiveness and Iatrogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…How frequently these adverse effects occur and outbalance the benefits of treatment is less clear. In particular, medication has been associated with a variety of adverse effects: paradoxical effects, manifestations of tolerance (loss of clinical effect, refractoriness), withdrawal symptoms and disorders [78][79][80][81]. Significant adverse effects of psychological treatments have been noted as well [82,83].…”
Section: Can Treatment Be Counterproductive?mentioning
confidence: 99%
“…Behavioral "toxicity" including oppositional perturbation: behavioral toxicity refers to the "pharmacological actions of a drug that, within the dose range in which it has been found to possess clinical utility, may produce alterations in mood, perceptual, cognitive and psychomotor functions, that limit the capacity of the individual or constitute a hazard to his/her well-being" ( [77], p.130). An important form of behavioral toxicity is "oppositional perturbation" that seeks to account for unintended and unwanted effects of medication on illness course, including symptom return after discontinuation, and a progressive loss of effectiveness (tachyphylaxis) across repeated anti-depressant medication trials [78][79][80][81]. Importantly, direct evidence for oppositional perturbation is lacking, but intriguing indirect evidence is available [78,79].…”
Section: Can Treatment Be Counterproductive?mentioning
confidence: 99%